Project evaluation of low-price housing development to support government program one milion house - Kusuma, Bryan; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2019)
Abstract – House backlog become government concern since 2010 until now, by creating program called one million houses program, giving opportunity for the citizen who really need the house but cannot afford it. Government program support all the party involved: banks, developers, contractors, and citizens. Problem that identify is on land price that increase nevery year making higher cost of development and time value of money that might have an impact on cash flow. Product positioning analysis using Porter’s five forces and strategy diamond and capital budgeting method using Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback Period (PBP) and Weighted Average Cost of Capital (WACC) method. Using 3 scenario case of different period shows that the highest investment return compares to discount rate of 11.28%, gain from selling all units in 1 year that on best scenario, shows IRR of 30%, NPV of IDR 2,678 million and Discounted PBP of 14 months. The conclusion shows project is feasible with positive cash flow, land permit become simplify and fast progress to complete, and government program provide tax incentive of 1%. Recommendation on Infrastructure, facility, and utilities support development can improve with electronic system management. Alternative suggestion to decrease construction interest rate.  Keywords: backlog, capital budget, government program, return of investment Abstract[B1]  – House backlog become government concern since 2010 until now, by creating program called one million houses program, giving opportunity for the citizen who really need the house but cannot afford it. Government program support all the party involved: banks, developers, contractors, and citizens. Problem that identify is on land price that increase nevery year making higher cost of development and time value of money that might have an impact on cash flow. Product positioning analysis using Porter’s five forces and strategy diamond and capital budgeting method using Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback Period (PBP) and Weighted Average Cost of Capital (WACC) method. Using 3 scenario case of different period shows that the highest investment return compares to discount rate of 11.28%, gain from selling all units in 1 year that on best scenario, shows IRR of 30%, NPV of IDR 2,678 million and Discounted PBP of 14 months. The conclusion shows project is feasible with positive cash flow, land permit become simplify and fast progress to complete, and government program provide tax incentive of 1%. Recommendation on Infrastructure, facility, and utilities support development can improve with electronic system management. Alternative suggestion to decrease construction interest rate.Keywords:backlog, capital budget, government program, return of investment [B1]Revised on Abstract following the change from Final Project